2008
DOI: 10.1128/jcm.00744-08
|View full text |Cite
|
Sign up to set email alerts
|

Streptobacillus moniliformis as the Causative Agent in Spondylodiscitis and Psoas Abscess after Rooster Scratches

Abstract: We report a case of Streptobacillus moniliformis spondylodiscitis accompanied by a psoas abscess in an 80-year-old man scratched by a rooster. S. moniliformis was identified from abscess fluid by use of 16S rRNA gene sequencing. After 18 weeks of antimicrobial therapy, the clinical condition of the patient improved. CASE REPORTIn 2005, an 80-year-old farmer was admitted to the university hospital of Clermont-Ferrand, France, for treatment of deterioration of his general health and inflammatory syndrome. In 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…Cases of limb-threatening or fatal infections caused by Campylobacter rectus have also been identified by 16S rRNA gene sequencing, which were rarely reported to cause invasive infections in the past (Lam et al, 2011). The technique has also been used to identify infections caused by rare Gram-negative bacteria, such as Streptobacillus moniliformis, Bordetella and Arcobacter, which may be difficult to diagnose by conventional methods (Chen et al, 2007;Dubois et al, 2008;Lau, Woo, Teng, et al, 2002;Tang, Ellis, et al, 1998;Woo, Chong, et al, 2001).…”
Section: Defining Disease Associations and Epidemiologymentioning
confidence: 96%
“…Cases of limb-threatening or fatal infections caused by Campylobacter rectus have also been identified by 16S rRNA gene sequencing, which were rarely reported to cause invasive infections in the past (Lam et al, 2011). The technique has also been used to identify infections caused by rare Gram-negative bacteria, such as Streptobacillus moniliformis, Bordetella and Arcobacter, which may be difficult to diagnose by conventional methods (Chen et al, 2007;Dubois et al, 2008;Lau, Woo, Teng, et al, 2002;Tang, Ellis, et al, 1998;Woo, Chong, et al, 2001).…”
Section: Defining Disease Associations and Epidemiologymentioning
confidence: 96%
“…However, the BD BACTEC PEDS PLUS/F which was used in the present case contains only 0.02% sodium polyanethol sulfonate and this concentration has been reported to allow the isolation of S. moniliformis [8,9] . The diagnosis of S. moniliformis infection has also been made recently using PCR [10] . However, the gold standard remains isolation of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,97,[102][103][104] The method by Boot et al 102 amplified a 296 bp fragment and showed considerable sensitivity but also some flaws in specificity due to amplicon sequence similarities with Leptotrichia sp., Fusobacterium necrogenes and Sebaldella termitidis. 102,103 Although these non-specificities could be solved by macro restriction with the endonuclease BfaI, Kimura et al 10 advanced this PCR with respect to specificity by improving oligonucleotide primers according to Table 3.…”
Section: Species Specific Pcr For S Moniliformismentioning
confidence: 99%